Alysicarpus gautalensis (Leguminosae: Desmodieae), a new species from Maharashtra, India - Gholami, Akram; Pandey, Arun K. (Phytotaxa, 2016)
Alysicarpus gautalensis, a new species of legume, is described from Maharashtra, India. It differs from A. bupleurifolius in having glabrous branches, elliptic-oblong, obtuse leaves with ciliate margins and trichomes present on both surfaces, lobes of the calyx ciliate, pods 2–6 jointed, moniliform with a foveo-rugulate surface sculpturing.